MIGRATION PROCESSES OF RURAL YOUTH: CAUSES, DIRECTIONS, PROBLEMS AND PROSPECTS - nova, Raisa I. Plato; Olesova, Marianna M.; Platonova, Agafya Z.; Storozheva, Nadezhda N.; Evseeva, Maria M.; Svechnikov, Vladimir A.; Hledko, Yuliya A. (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the topic is determined by the need to study the socio-economic development of rural areas and study the reasons for the outflow of young people from rural areas to cities. This process has negative demographic consequences, because it is young people who are the most able-bodied part of the population, this age is the most reproductive and accounts for most of the birth of children. The aim of the study is to analyze the migration processes of rural youth. As a research method, the method of interviewing experts, heads of administrations of rural settlements was chosen, which allows studying the causes and directions of migration of rural youth and identifying the most urgent problems. The article considers the characteristics of migration and migrants in rural settlements; identifies factors that affect migration processes; identifies the main causes of migration of young people in rural areas. The novelty and originality of the study lies in the fact that for the first time migration processes in rural areas were analyzed from the point of view of experts. It is noted that the population of the village is aging, due to various reasons: local youth move to live in the city, the birth rate decreases, and the share of the working-age population decreases. For the first time, the reasons for the outflow or influx of young people in rural areas are analyzed from the point of view of the heads of districts. It is shown that young people leave due to lack of prospects, while young people are not stopped by the difficulties that they may encounter (everyday difficulties, lack of friends and acquaintances in the new place of residence); the requirements of young people for education (most young people seek higher education); the difficulties of finding jobs in rural areas, according to the received education. It was revealed that experts consider the impact of transport accessibility on the migration of young people insignificant, since young people are the most mobile segment of the population; many have their own transport and move independently. It is shown that young people remain in the village, since everything in the village is static and familiar from childhood. In addition, it is noted that the opposite process is currently observed - young people and able-bodied people who are tired of living in the city, move back to the village, to their small Homeland. It is shown that the percentage of increase in the number of rural settlements is due to migrants. The factors of attractiveness of life in rural areas are highlighted: the availability of relatively cheap housing in rural areas; natural conditions. It is highlighted that agricultural production needs working youth, despite the progress and mechanization of manual labor, there are still very popular professions in the village: locksmiths, turners, machine operators, welders, veterinary doctors. It is determined that the main reasons that hinder the employment of young people in the settlements, experts consider the discrepancy between the received education to the requirements of the vacant place. It is noted that recently there is a shortage of teachers, doctors, and specialized cultural workers